Motywy oczu, ślepoty i światła w późnej twórczości Czesława Miłosza - Dobrzyńska, Teresa (Colloquia Litteraria, 2011)
The subject of the examination here is a late period of Miłosz’s literary output (volumes: „Druga przestrzeń” and „Wiersze ostatnie”). While discussing the motif of eyes, blindness and light the author brings up a general and serious problem of the poet’s vision in his final poems: he uses this theme in existential and metaphysical contexts.